2021
DOI: 10.1177/11297298211015088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indwelling centrally inserted central catheter on tip location of peripherally inserted central catheter with intracavitary electrocardiogram guidance: A retrospective case-control study

Abstract: Background: Intracavity electrocardiogram (IC-ECG) guidance is an effective technology for monitoring the tip locations of centrally inserted central catheters (CICCs) and peripherally inserted central catheters (PICCs). However, for patients with an indwelling CICC, there has been no study on whether the CICC affects PICC tip positioning with IC-ECG guidance. Methods: Thirty people with a CICC requiring PICC insertion, matched with age to controls without a CICC. The stability of IC-ECG waveforms, the amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…At the same time, the scope of use of ECG guidance is constantly increasing in connection with clinical research and former limits of the system may be alleviated. Even if active magnetic device such as ventricular assist device are still problematic for ECG guidance (63), concomitant indwelling central catheters has been proved not to affect tip positioning (64). Also it has been showed that patients presenting abnormal surface ECG such as atrial fibrillation may be successfully managed through the use of ECG guidance (65).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the scope of use of ECG guidance is constantly increasing in connection with clinical research and former limits of the system may be alleviated. Even if active magnetic device such as ventricular assist device are still problematic for ECG guidance (63), concomitant indwelling central catheters has been proved not to affect tip positioning (64). Also it has been showed that patients presenting abnormal surface ECG such as atrial fibrillation may be successfully managed through the use of ECG guidance (65).…”
Section: Discussionmentioning
confidence: 99%